Aboveground Biomass Allometric Equations and Fuelwood Properties of Six Species Grown in Ethiopia - Fantu, Woldeyohanes (2005)
In Ethiopia, plantations of fast growing species are being established to increase the supply of wood; especially for the biomass fuel consumption. In order to better inventory the supply of biomass, allometric equations and fuel properties need to be determined. The objectives of this study were i) to develop regression equations of tree component from six species ii) to determine fuel properties and fuel value index (FVI) of the six tree species and iii) to compare combustion characteristics of tree component of the six species using thermogravimetric analysis (TGA).